PENEGAKAN HUKUM DALAM KASUS KECELAKAAN LALU LINTAS DI SATLANTAS POLRES BOYOLALI - WINARNO, JOKO (Dinamika Hukum, 2016)
The purposes of this research is to study and analyzed the law enforcementin the Case of Traffic Accident and the steps conducted by Satlantas (Unit ofTraffic), therefore, the implementation of investigation can took place fast.Backgoround. The measurement of the accident incident is through thepoliceâ€™s act of who respond fast either in an accident, a crime, or other incidentsthat need a presence of Police. In order to anticipate this matter, recently, Police ofThe Republic of Indonesia has a center of information controlling which issophisticated enough, therefore, based on the underlying background, the writertake a title â€œLaw Enforcement in The Case of Traffic Accident in Satlantas PolresBoyolaliâ€.In this research, the location where the research took place is PolresBoyolali (Boyolali Police) because of being based on the consideration that inPolres Boyolali. Type of the research used in this research is a juridical empiricresearch. The characteristics of the research conducted by the writer is descriptivethat is a research which tries to describe situation and other symptoms. Thetechnique of data analysis is a technique in checking and analyzing the data sothat valid and reliable data can be obtained. In this research, the writer used aqualitative method.The process of law enforcement conducted in the traffic accident can beconcluded that the act of the suspect EDY SURYO PITOYO bin MUSLIMIN,Age: 26 y.o, Place of Birth in Magelang on 24 August 1989, Religion: Islam,Gender: Male, Last Education: Junior High School, Occupation: Private Worker,Address: Dk. Kalangan, Rt 05/02, Ds/Kec. Grabag, Kab. Magelang had met theelement of offense contained on the Article 310 paragraph (3) Act Number 22 of2009 concerning Traffic Light and Road Transportation explaining that: Everyonewho drive a vehicle that due to his/her carelessness causes a traffic accident inwhich the victim is heavily injured as meant by Article 310 paragraph (3), he/shewill be punished with imprisonment for maximally 5 (five) years and/or fine asmuch as IDR 10,000,000.00 (ten million Rupiah). That in Article 310 paragraph(3) Act Number 22 of 2009 concerning traffic and road transportation explains:Everyone who drive a vehicle that due to his/her carelessness causes a trafficaccident in which the victim is heavily injured is punished with imprisonment formaximally 5 (five) years or fine as much as IDR 10,000,000 (ten million Rupiah).The elements of Article : a. Everyone who drive a vehicle, b. Due to his/hercarelessness causes a traffic accident, c. Causing the victim heavily injured.Keywords: Law enforcement, Traffic Accident